A Study on the Basic Variables of Organizational Exclusion: A University Example (Third Sector Social Economic Review, 2025)
This study aims to examine the phenomenon of organizational exclusion in higher education institutions through the experiences of academic staff. Human beings inherently seek belonging and acceptance; when these needs are not met, individuals are likely to experience a sense of exclusion. Organizational exclusion is a significant organizational behavior problem that negatively affects employees’ psychological well-being, motivation, and performance. However, the literature remains limited in addressing this phenomenon within the unique context of higher education institutions.A qualitative research method was adopted, employing a phenomenological design. Semi-structured interviews were conducted with 23 academics working at a public university in Turkey, and the responses of 15 participants who had experienced exclusion were analyzed using descriptive analysis. The findings reveal that organizational exclusion predominantly manifests in the forms of intellectual segregation (e.g., exclusion from research projects and publication processes) and institutional distance (hierarchical relations and decision-making mechanisms). Moreover, exclusion was found to lead to psychosocial consequences such as motivational erosion, reduced productivity, and burnout. Participants reported coping strategies such as building solidarity networks, self-motivation, and utilizing institutional mechanisms.This study contributes to the literature by providing a comprehensive perspective on organizational exclusion in the higher education context. Furthermore, it offers practical implications for fostering inclusive cultures, transparent communication, and fair management policies in universities.
Keywords: Organizational Exclusion; Workplace Ostracism; Academic Staff; higher education institutions; Organizational Behavior